# algebra 1

Given sets X = {0, 1, 2, 4}, Y = {0, 2, 4, 6, 8}, and Z = {5, 6, 10}, which of the
following statements is false ?
[A] 2�¸X [B] 6�¸Y [C] 10�¸Z [D] 2∉Y [E] None of these

i think it is C can you tell me if i am right

thanks in advance

1. 👍 0
2. 👎 0
3. 👁 92

## Similar Questions

1. ### Business Math

Being inventory of 12 sets of paints at a cost of \$1.50 each. During the year the store purchased 4 sets at \$1.60, 6 sets at \$2.20, 6 sets at \$2.50, and 10 sets at \$3.00. By the end of the year, 25 sets were sold. Caculate the

asked by Jean on December 26, 2012
2. ### math

Marvin Company has a beginning inventory of 12 sets of paints at a cost of \$1.50 each. During the year, the store purchased 4 sets at \$1.60, 6 sets at \$2.50 and 10 sets at \$3.00. By the end of the year, 25 sets were sold.

asked by Anonymous on November 17, 2011
3. ### URGENT! discrete math help please

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ B - for all sets A,B and

asked by Mary on February 27, 2014
4. ### math. Somebody help urgently please

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ B - for all sets A,B and

asked by Mary on February 27, 2014
5. ### Somebody please help urgently!

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ B - for all sets A,B and

asked by Mary on February 27, 2014
6. ### math

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ B - for all sets A,B and

asked by Mary on February 27, 2014
7. ### URGENT HELP WITH DISCRETE MATH PLEASE

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ B - for all sets A,B and

asked by Mary on February 27, 2014
8. ### math help

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ B - for all sets A,B and

asked by Mary on February 27, 2014
9. ### discrete math help please

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ B - for all sets A,B and

asked by Mary on February 25, 2014
10. ### math

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ B - for all sets A,B and

asked by Mary on February 26, 2014
11. ### discrete math help please

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ B - for all sets A,B and

asked by Mary on February 26, 2014

More Similar Questions